Human right to the health in the penitentiary and prison establishment of Tunja, Colombia - Rodríguez Forero, Nicolas David (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This qualitative, research aims to analyze the scope of protection, recognition and access to health services for people deprived of liberty at the Medium Security and Prison Establishment in Tunja, Colombia during the 2005-2018 period. This objective involves the participation of the state, municipal, and control agencies such as Municipal Ombudsman, the Ombudsman and the Attorney General of the Nation, in order to demand the provision of medical-care services, within the framework of the State of Things Unconstitutional and Prison Emergency. The method used in this sense was the documentary analysis of two types of sources: a) the review of authors on the evolution of the right to health in prison matters, and b) the deficit and emergence of the prison health care model. The results show that the EPMSC of Tunja is one of the least crowded prison settings in the country, wich it has had a scope and scenario of denial, weak and tenuous to satisfactory, favoring the participation of the HR committee, and mainly depending on the balance economic model of health care. Consequently, it implies that sustainability and infrastructure must be required in the Tunja prison scenario, for the guarantee and enforceability of the human right to health.